1994
DOI: 10.1128/iai.62.2.704-708.1994
|View full text |Cite
|
Sign up to set email alerts
|

Protection of human respiratory epithelium from Pseudomonas aeruginosa adherence by phosphatidylglycerol liposomes

Abstract: The ability of phosphatidylglycerol (DSPG) liposomes to prevent adherence of Pseudomonas aeruginosa to primary cultures of non-cystic fibrosis (CF) and AF508 homozygous CF human respiratory epithelium was studied. The culture model was characterized by the simultaneous presence of various cellular phenotypes: well-differentiated respiratory epithelial cells, ciliated and nonciliated cells, and migrating cells which can be assimilated into a regenerating epithelium after injury. DSPG liposomes significantly dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 27 publications
(34 reference statements)
1
3
0
Order By: Relevance
“…During spreading, which is the first event of epithelial regeneration, CF and non-CF respiratory epithelial cells bind a great number of P. aeruginosa organisms, with significantly greater bacterial adherence in CF cells than in non-CF cells. These results are in agreement with our previous data (8) and with the results of Zar et al (28), who suggested that the CFTR gene mutation leading to CFTR FIG. 3.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…During spreading, which is the first event of epithelial regeneration, CF and non-CF respiratory epithelial cells bind a great number of P. aeruginosa organisms, with significantly greater bacterial adherence in CF cells than in non-CF cells. These results are in agreement with our previous data (8) and with the results of Zar et al (28), who suggested that the CFTR gene mutation leading to CFTR FIG. 3.…”
Section: Discussionsupporting
confidence: 94%
“…The major bacterial adhesins implicated in epithelial adherence are pili (23). We and others have reported elsewhere (8,17,18) the unique tropism of P. aeruginosa for regenerating respiratory epithelial cells characterized by a spreading shape, which was previously identified during respiratory epithelial wound repair after injury (27). Following denudation of the extracellular matrix, the respiratory epithelium is rapidly able to regenerate.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…These cells, which display lamellipodia and long filopodia, characteristics of migratory cells (34), are involved in the processes of epithelium differentiation and repair following injury. It has been demonstrated previously (14) that P. aenuginosa adherence to migratory epithelial cells in culture was significantly greater than that to nonmigratory cells. We observed that these migratory cells were more sensitive to PA-I lectin than the other respiratory cells.…”
Section: Discussionmentioning
confidence: 89%